2018
DOI: 10.1016/j.jtho.2018.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Efficacy of Dual Blockade of EGFR Signaling by Osimertinib in Combination With Selumetinib or Cetuximab in Activated EGFR Human NCLC Tumor Models

Abstract: We showed that a dual vertical EGFR blockade with osimertinib plus selumetinib/cetuximab is a novel effective therapeutic option in EGFR-mutated NCLC and that hedgehog pathway activation and its interplay with MAPK is involved in resistance to these combination treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
(59 reference statements)
2
25
0
Order By: Relevance
“…Osimertinib resistant can occur via oncogenic shift to alternative RTKs including c-MET (11), HER2 and/or HER3 (7-9), IGF1R (12), and AXL (13)(14)(15)(16). The variety of RTK bypass pathways that can lead to osimertinib resistance suggests that broad inhibition of RTK signaling may be a more effective therapeutic strategy than any individual RTK inhibitor to limit Combining osimertinib with a MEK inhibitor can enhance osimertinib efficacy (10,17,20,56,57) and Phase II clinical trials are currently underway to assess combining osimertinib with the MEK inhibitor selumetinib in EGFR-mutated NSCLC (NCT03392246), although resistance to combined osimertinib and MEK inhibition still occurs (17). In a recent study designed to understand resistance to combined osimertinib and MEK inhibition, Kurppa et al (2020) show that combining osimertinib with the MEK inhibitor trametinib results in EGFRmutated cells entering a senescent state that is dependent on the activation of the Hippo pathway effector YAP and its transcription factor binding partner TEAD (58).…”
Section: Discussionmentioning
confidence: 99%
“…Osimertinib resistant can occur via oncogenic shift to alternative RTKs including c-MET (11), HER2 and/or HER3 (7-9), IGF1R (12), and AXL (13)(14)(15)(16). The variety of RTK bypass pathways that can lead to osimertinib resistance suggests that broad inhibition of RTK signaling may be a more effective therapeutic strategy than any individual RTK inhibitor to limit Combining osimertinib with a MEK inhibitor can enhance osimertinib efficacy (10,17,20,56,57) and Phase II clinical trials are currently underway to assess combining osimertinib with the MEK inhibitor selumetinib in EGFR-mutated NSCLC (NCT03392246), although resistance to combined osimertinib and MEK inhibition still occurs (17). In a recent study designed to understand resistance to combined osimertinib and MEK inhibition, Kurppa et al (2020) show that combining osimertinib with the MEK inhibitor trametinib results in EGFRmutated cells entering a senescent state that is dependent on the activation of the Hippo pathway effector YAP and its transcription factor binding partner TEAD (58).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with a previous report stating that Cet was an efficient tumor-targeting moiety by binding to EGFR excessively expressed on the surface of colorectal cancer cells. 33…”
Section: Cellular Uptakementioning
confidence: 99%
“…NSCLC cells with acquired resistance to EGFR TKIs have a high level of Smo expression, through Smo amplification [ 127 ]. Della-Corte et al used in vivo xenograft models of EGFR mutated NSCLC treated with third-generation EGFR TKI (osimertinib) in association with a Mek inhibitor (selumetinib) [ 128 ]. They showed that Shh pathway is involved in resistance to this combo treatment, and that inhibition of Shh pathway inhibits proliferation, cell migration, and invasive properties of ex vivo resistant cultured cells.…”
Section: Shh Pathway and Resistance To Tyrosine Kinase Inhibitorsmentioning
confidence: 99%